PENGARUH BRAND IMAGE DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK LA TULIPE DI KOTA PADANG - Tria Anggina Putri; Marwan Marwan; Rose Rahmidani (Universitas Negeri Padang, 2018)
Abstract: This research aims to know and prove how much influence the brand image and perceived quality of La Tulipe Cosmetic to Purchase Decision in Padang City. This research is a causal type of research, using primary data obtained through questionnaires and using multiple regression analysis. The population observed as a sample was 100 female respondents aged 20 - 59 years in Padang City. Data (samples) Analysis using SPSS version 21.00. The results of this study indicate that: 1) brand image and perceived quality significantly together influence the decision to purchase cosmetic product La Tulipe. 2) brand image has no significant effect on the purchase decision of La Tulipe cosmetic products in Padang City. 3) perceived quality has a significant positive effect on purchasing decisions.Keyword: Purchasing Decision, Brand Image, Perceived Quality